PENGARUH KEMANDIRIAN BELAJAR DAN KEMAMPUAN AKADEMIK TERHADAP KEMAMPUAN BERPIKIR KRITIS DIMEDIASI OLEH EFIKASI DIRI - wira suciono, - (2021)
This objective is to see and analyze learning abilities and academic abilities against self-mediated critical thinking skills. This study uses an explanatory survey method with a quantitative approach. Data collection was carried out by distributing questionnaires. The population in this study were all students of class X State Senior High School (SMA) in the City of Tasikmalaya who were assessed as 3,756 students. Based on Slovin calculations with an error of 5% obtained a sample of 360 students with proportional random sampling technique. The data that has been collected is then analyzed using the descriptive analysis technique and path analysis (Path Analysis). The results showed that 1) the variables of learning independence, academic ability and self-ability were in the good category. 2) Independent learning had a positive and significant effect on students' critical thinking skills. 3) Self-efficacy mediates the effect of independent learning on students' critical thinking skills. 4) academic ability has a positive and significant effect on students' critical thinking skills. 5) Self-efficacy mediates academic ability towards students' critical thinking skills and 6) Self-efficacy is the ability to learn and academic abilities.